Orientalism Reversed: Images and Perceptions of the EU in the Philippines - Salvador, Alma Maria O (Archīum Ateneo, 2009)
The following sections are included: ORIENT AND OCCIDENT: EU–PHILIPPINE RELATIONS VIEW FROM THE SIDES: EU IMAGERY IN THE NEWS MEDIA IN THE PHILIPPINES Selected Media EU Media Visibility EU Framing in Media Sources Evaluation of the EU in Media Sources EU Perceptions among the Newsmakers in the Philippines VIEW FROM THE TOP: STAKEHOLDERS' PERCEPTIONS OF THE EU The Importance of Different Regions to the Philippines (in the Present and in the Future) EU as a Great Power EU as an International Leader Relations between the EU and the Philippines State of Relations Euro Perceptions of the EU's Enlargement ASEM Spontaneous Images of the EU Sources of Information VIEW FROM BELOW: EU PERCEPTIONS IN THE PHILIPPINE PUBLIC OPINION EU Partnership with the Philippines Images of Europe Development Actors and ASEM Nature of Ties with Europe SO WHAT? CONCLUSIONS AND RECOMMENDATIONS